Flexural capacity prediction of composite RC members strengthened with UHPC based on existing design models. (February 2020) - Shirai, Kazutaka; Yin, Hor; Teo, Wee
Abstract: Ultra-high-performance concrete (UHPC), a new generation of cementitious materials with very high strength, ductility, and durability, has been used for enhancing reinforced concrete (RC) structures as a strengthening material. The structural performance of RC members strengthened by UHPC or UHPC-concrete composite members is significantly improved. However, there are few methods for predicting the capacity of UHPC-concrete composite members. The present study proposes a simple method based on existing design models for the prediction of the flexural strength of composite RC members strengthened with UHPC at the tension zone. Rectangular stress block diagrams are used for the compression and tension zones of the conventional concrete and UHPC layers, respectively, in a composite section. The prediction results show good agreement with experimental results. The failure modes are predicted and compared with those observed in an actual test. Furthermore, a parametric study is carried out by varying some parameters, including the thickness of the UHPC layer and the compressive strength of UHPC. The results show that the proposed method can predict the flexural strength of UHPC-concrete composite members.